Implementasi Layanan Pajak Daerah Berbasis Online Pada Badan Pendapatan Daerah Kabupaten Kutai Kartanegara : Perspektif Dynamic Governance - Enos Paselle; Fathul Alamin; Harun Harun; Muhammad Adha Khalilullah; Rabiatul Adawiyah; Suka Madeyanto (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2024)
The efforts made by the Kutai Kartanegara Regency Government in managing regional taxes start from exploring tax potential, tax data collection and assessment, and billing, as well as other efforts in optimizing revenue from the Regional Tax sector such as the use of technology and information to support the acceleration and ease of implementing tax administration management as well as providing convenience in providing service accessibility to the community in the context of modernizing tax administration and realizing regional fiscal independence. Qualitative research conducted regarding the dynamic governance perspective in the implementation of online-based Regional Tax services proves that the application of culture and capability elements can be a supporting factor in the successful implementation of the Online Tax service program at the Regional Revenue Agency of Kutai Kartanegara Regency. Although the formation of an appropriate work culture requires a long time, there is a need to strengthen socialization which is an important part of optimizing the implementation of this program.